Human Umbilical Vein Smooth Muscle Cells as a Model to Study Thrombin Generation and Function: Effect of Thrombin Inhibitors - Catalioto, Rose-Marie; Cucchi, Paola; Renzetti, Anna Rita; Criscuoli, Marco; Subissi, Alessandro (Thrombosis and Haemostasis, 1996)
The aim of the present work was to study how human umbilical vein smooth muscle cells (HUVSMC) can initiate the coagulation process and to investigate the responses of these cells to thrombin. Exposure of HUVSMC to recalcified human plasma led to a time-dependent production of thrombin, measured both as amidolytic activity and as release of fibrinopeptide A. Thrombin activity was dose-dependently reduced by an anti-human tissue factor antibody (76 ± 3% at 10 Μg/ml) and by inhibitors like heparin, rec-hirudin, hirulog-1, Napap and hiru-norm, a novel hirudin-like thrombin inhibitor (IC50 = 2 ± 0.4, 8 ± 1, 130 ± 22, 199 ± 29 and 68 ± 8nM, respectively). The release of fibrinopeptide A was similarly prevented (IC50 = 14 ± 1,132 ± 25 and 50 ± 8 nM for rec-hirudin, Napap and hirunorm, respectively). Exogenously added thrombin increased thymidine incorporation into HUVSMC to 240 ± 30% of basal (EC50 = 0.49 ± 0.09 nM) and thrombin inhibitors blocked this effect (IC50 = 10 ± 3, 37 ± 17, 343 ± 165 and 1402 ± 758 nM for rec-hirudin, hirunorm, Napap and hirulog-1, respectively). Also recalcified human plasma was mitogenic for HUVSMC and its effect was mainly due to endogenously generated thrombin, as shown by the use of thrombin inhibitors. In conclusion, HUVSMC are capable of initiating the extrinsic coagulation cascade, leading to the formation of thrombin which promotes clotting and stimulates DNA synthesis. Thrombin inhibitors prevent both coagula-tive and cellular effects of thrombin.